1999
DOI: 10.1007/s12043-999-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in Langmuir monolayers

Abstract: Some fatty acids, lipids, polymers and mesogenic molecules which are amphiphilic in nature spread at the air-water interface to form stable Langmuir monolayers. They exhibit a rich variety of two-dimensional (2D) phases. In this article, we briefly review some of the novel features we have found in these monolayers. For example, we find transition from a 2D monolayer to threedimensional structures possessing liquid crystalline order, induced liquid condensed phase, demixing of liquid expanded phase, critical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A better understanding of the factors involved in the formation of block copolymer surface micelles would be of great interest for the development of block copolymer-based nanoscale templates for nanolithography and biosensing devices and for microporous and mesoporous structure development. The surface film balance method for the study of surface monolayers is a technique that is particularly useful for the determination of molecular organization. , In the present study, triblock copolymers with different PS/PEO ratios were studied by film balance technique and atomic force microscopy (AFM). Characteristics of the self-assembled structures are discussed, and a simple geometrical model is proposed to describe the scaling of the surface micelle dimensions formed by PEO-PS-PEO diblock and triblock copolymers with molecular parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the factors involved in the formation of block copolymer surface micelles would be of great interest for the development of block copolymer-based nanoscale templates for nanolithography and biosensing devices and for microporous and mesoporous structure development. The surface film balance method for the study of surface monolayers is a technique that is particularly useful for the determination of molecular organization. , In the present study, triblock copolymers with different PS/PEO ratios were studied by film balance technique and atomic force microscopy (AFM). Characteristics of the self-assembled structures are discussed, and a simple geometrical model is proposed to describe the scaling of the surface micelle dimensions formed by PEO-PS-PEO diblock and triblock copolymers with molecular parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Various studies have reported isotherms where a number of states and the equilibrium between them have been clearly identified as the monolayer is compressed. [4][5][6] When the area per molecule is very large, the monolayer is in a vapor phase ͑V͒. Isothermal compression generates a transition from the vapor phase to a liquid expanded state ͑LES͒.…”
Section: Introductionmentioning
confidence: 99%